Exploration of differentiation standard for primo through the histological common point of threadlike structure found in rats and swine - Sun Hee Yeon; O. Sang Kwon; Seong Jin Cho; Suk Yun Kang; Ji Young Moon; Yeonhee Ryu (Integrative Medicine Research)
Background: The novel threadlike structure is called the primo structure, and studies are conducted through many different approaches. Although various ways of differentiation are currently used, a standard for differentiation is deemed necessary in order to identify the primo structure based on the overall form of the structure. This study aims to explore the differentiation standard through the histological common point of the threadlike structure of rat and swine by using the hematoxylin and eosin (H&E) staining method commonly used for histological research in various structures. Methods: An 8-week old Sprague-Dawley rat and a Yorkshire pig weighing 30–40 kg were used. A total of 65 pieces of rat threadlike structure and 100 pieces of swine threadlike structure were collected after the abdomen was cut and opened. The following three different characteristics were confirmed using the H&E staining method for the collected structures: (1) bright cell availability; (2) cavity availability; and (3) nuclei density. Results: For the rat threadlike structure, the bright cell (70.5%) and nuclei density (92.6%) were mainly observed; in the swine threadlike structure, however, the bright cell (60.6%) and cavity (67.2%) were mainly observed. The bright cell was confirmed to have been observed in the threadlike structures of both rat and swine. Conclusion: The bright cell is determined to be the common point in the primo structure. However, further research is deemed necessary in the future as to the functions performed by the characteristic shown by the Primo structure.